Correlation between School Culture and Islamic Religious Education (PAI) Learning on Student Character Formation - Salik, Yunus (Lembaga Kajian dan Penerapan Nilai - Nilai Islam Unissula, 2025)
The development of national character can be done through the development of one's individual character. However, because humans live in a certain social and cultural environment, the development of a person's individual character can only be done in the relevant social and cultural environment. That is, the development of culture and character can be carried out in an educational process that does not release students from the social environment, community culture, and national culture. The research used is ex post facto, where the researcher connects causes and effects that are not manipulated or treated (designed and implemented) by the researcher. PAI learning is significantly related to the character of students, because the value of p = 0.000 is smaller than 5%. The correlation criterion is very strong (ry 1.2 = 0.886). Thus, school culture and PAI learning are related either independently or not with the character of the students of Madrasah Aliyah Negeri Palopo. The most dominant variable influencing the student's character is the PAI learning variable. Based on the hypothesis test, it was concluded that school culture and PAI learning together had a positive effect on the character of junior high school students. There is a positive influence between school culture and PAI learning with student character, this shows that student character will increase if school culture and PAI learning at Madrasah Aliyah Negeri Palopo. Based on the hypothesis test, it was concluded that school culture and PAI learning together had a positive effect on the character of junior high school students. There is a positive influence between school culture and PAI learning with student character, this shows that student character will increase if school culture and PAI learning at Madrasah Aliyah Negeri Palopo. Based on the hypothesis test, it was concluded that school culture and PAI learning together had a positive effect on the character of junior high school students. There is a positive influence between school culture and PAI learning with student character, this shows that student character will increase if school culture and PAI learning at Madrasah Aliyah Negeri Palopo.